A novel one-pot microwave assisted green synthesis of pyridinyl-1,3,5-triazine-2,4-diamine hybrids as potent antimicrobial agents - Omniya Sayed Zaky; Mohamed Hisham; Mohamed Abd-Elmonem; Ramadan Yahia; Laila Abdulmohsen Jaragh-Alhadad; Ramadan Ahmed Mekheimer; Gamal El-Din A. Abuo-Rahma; Moustafa Sherief Moustafa; Manal Makboul Ebied; Kamal Usef Sadek (BMC Chemistry)
Abstract A novel, green, and efficient microwave-assisted synthesis of pyridinyl-1,3,5-triazine-2,4-diamine hybrids was developed using a one-step, multi-component reaction involving 2-aminopyridine, cyanamide, and aromatic aldehydes/ketones or cyclic ketones under neat reaction conditions. This method offers a simple, high-yield, and environmentally friendly approach with excellent atom economy. In contrast to traditional, more hazardous methods, this process significantly reduces reaction time and complexity. In vitro antimicrobial evaluation revealed that most synthesized compounds exhibited no significant activity against Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae, except compound 7b, which showed efficacy against Klebsiella pneumoniae (MIC = 100 µg/mL). Notably, compounds 6a, 6 g, 7b, and 8 displayed antibacterial activity against Proteus mirabilis, and compounds 6c, 7b, and 7c showed antifungal activity against Candida albicans. Docking simulations demonstrated favorable interactions of compounds 6a and 6 g with the urease enzyme, suggesting their potential as bacterial urease inhibitors. Molecular dynamics simulations of the 6 g-urease complex over 25 ns demonstrated stable ligand binding, minimal structural perturbations, and strong interactions with key active site residues, confirming the complex's stability and integrity. ADMET analysis confirmed favorable drug-like properties, including high gastrointestinal absorption and skin permeability, with some compounds displaying central nervous system activity. The Structure–Activity Relationship (SAR) analysis indicated that both triazine and pyridine moieties are critical for enhancing antibacterial properties, particularly through improved binding with the urease enzyme, with hydrophobic substituents and cyclohexyl groups further optimizing antimicrobial efficacy.